(untitled) (Modern education and development, 2025)
Globally, women are moving into a growing space as innovators, entrepreneurs, startup founders, technologists, businesswomen, and homemakers. From their existing roles in traditional economic sectors such as agriculture, healthcare, education, and more, women are entering the Fourth Industrial Revolution to drive global and regional knowledge economies. The idea of ​​women as drivers of a country’s economy can be captured by “Womenomics,” a term coined by Goldman Sachs strategist Katie Matsui and introduced by Japanese Prime Minister Shinzo Abe in 2013 to stimulate his country’s economic growth. Womenomics is not only a good social movement, it is also good for business: increasing women’s equality could add 12 trillion to global GDP by 2025.